Comparação de modelos para o cálculo da porosidade local em simulações CFD-DEM de um leito fluidizado líquido - Ogasawara, Enos Yuiti (Universidade Federal de São Carlos, 2021)
In the present study, a liquid fluidized bed was simulated using the Unresolved CFD-DEM approach, evaluating the application of three local void fraction calculation methods with six refinement levels for the mesh used in the simulations. Different fluid flow rates were tested for the possible combinations between method and mesh refinement levels: 35 L/min, 55 L/min and 75 L/min. The CFDEM®coupling software was used for the simulations. For the results analysis, the average void fraction values obtained in the simulations were compared to the values predicted by the Richardson-Zaki empirical equation. The local pressure fluctuation and the net mass flow rate were also monitored. Finally, the most satisfactory method applied was identified, as well as the most satisfactory mesh refinement level. Based on the results, it is recommended, for this solid-fluid flow, the use of the so called ‘Divided’ method with the 5-5-120 mesh, specifically regarding the agreement with the Richardson-Zaki equation, in which the errors presented were 1,35%, -1,42% and -1,39% for the flow rates of 35 L/min, 55 L/min and 75 L/min, respectively. In addition, the ‘Divided’ method also showed superior stability with respect to the local pressure fluctuation, once the average pressure values, for a given flow rate, were more similar between different grid refinement levels compared to the other local void fraction calculation methods, the ‘Divided’ method also showed smaller standard deviation in pressure fluctuations when compared to the other methods. Concerning the net mass flow rate, the conclusions conflicted. With 75 L/min, it can be observed that the bigger the mesh refinement level, the smaller the errors, for all methods. With 55 L/min, the 5-5-120 to 8-8-180 meshes showed better results, while for 35 L/min, the best result was observed for the 4-4-100 mesh.
Comparison of models for calculating local porosity in CFD-DEM simulations of a liquid fluidized bed
Keywords: Fluidodinâmica computacional; Método dos elementos discretos; Esquemas de acoplamento; Leito fluidizado líquido; Computational Fluid Dynamics; Discrete element method; Coupling schemes; Liquid fluidized bed; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA